Topology Management System for Wireless Local Area Network - Xuegang Ma (Dianxin kexue)
When the WLAN network faults, maintenance personnel need to quickly locate and solve the fault,to serve the operator's network operation better. Therefore, a topology management system for WLAN fault location network management system was proposed. The management system has been put into operation and has achieved the expected effect,provides a powerful support to WLAN network fault management of operators.